Work of a nurse in a health centre treatment room. Issue 5678 (1st November 1969) - Dixon, P. N.
Abstract : In six months there were 1, 704 attendances at the treatment room of a small health centre. The attendance rate for the population registered with the health centre doctors was 448 per 1, 000 patients per year. Females between 15 and 44 years and males under 15 had the highest attendance rates. There were 256 casual attenders, 58 (23%) of whom were referred to a doctor or hospital for further advice or treatment. It is suggested that in a health centre treatment room about six hours of nursing time a week for every 1, 000 patients is required, and that a case can be made out for some of the routine work of casualty departments being done in health centres.